Understanding collapse ancient history and modern myths - Middleton, Guy ca. 20./21. Jh (Cambridge University Press, 2017)
"Understanding Collapse explores the collapse of ancient civilisations, such as the Roman Empire, the Maya, and Easter Island. In this lively survey, Guy D. Middleton critically examines our ideas about collapse...how we explain it and how we have constructed potentially misleading myths around collapses...showing how and why collapse of societies was a much more complex phenomenon than is often admitted. Rather than positing a single explanatory model of collapse...economic, social, or environmental...Middleton gives full consideration to the overlooked resilience in communities of ancient peoples and the choices that they made. He offers a fresh interpretation of collapse that will be accessible to both students and scholars. The book is an engaging, introductory-level survey of collapse in the archaeology/history literature, which will be ideal for use in courses on the collapse of civilizations, sustainability, and climate change. It includes up-to-date case studies of famous and less well-known examples of collapses, and is illustrated with 25 black and white illustrations, 3 line drawings, 16 tables and 18 maps"...